Development of a Learning Module to Interpret Engineering Drawings Using Augmented Reality (AR) for Vocational High School Students - Zuhdi Mizian; Sofyan Sofyan; Saharrudin Saharrudin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Interpreting engineering drawings is a fundamental competency for vocational high school students preparing for industrial careers. However, conventional instruction often fails due to students’ difficulty in visualizing 3D objects from 2D representations, limited interactive learning tools, and low motivation. This study aimed to develop an Augmented Reality (AR)-assisted learning module to enhance the effectiveness and interactivity of engineering drawing instruction. The research employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model of Research and Development (RD), involving material experts, media specialists, instructional designers, teachers, and vocational students. The developed module was evaluated for feasibility and effectiveness. Expert assessments rated the module as "Very Feasible," with scores from material experts (96.80%), media experts (77.00%), and instructional design experts (93.80%). A limited implementation trial demonstrated a significant improvement in student understanding, indicated by an N-gain score of 0.71 (high category). Additionally, 89.3% of students reported high satisfaction with the module. The findings suggest that the AR-assisted module effectively enhances students' ability to interpret engineering drawings. This development presents an innovative alternative to conventional methods and demonstrates the potential of AR integration to create engaging, interactive learning environments in vocational education settings.